Cultivation of gladiolus bring cheers in coastal Tamil Nadu - Ganesan, Thiru. S.; Nazir, Manoj; Poravin, T. Raj; Nazir, Manoj (Indian Horticulture, 2019)
In years to come, with the active participation of hard working, innovative farmers like Thiru. S. Ganesan, colour revolution initiated in coastal farming system of Tamil Nadu will not be a distant dream but a near reality in progress bringing economic prosperity and progress to all the coastal farming communities. The growth of service sector, high priority given to the farm sector by the central and state governments will also aid in this innovative farm enterprise thereby raising the standard of living of small and marginal coastal farmers of our nation.